The Utilization of Artificial Intelligence in Developing Instructional Media at Pesantren Agrobusiness Tunas Quran, Bandung Regency - Dendi Gusnadi; Eva Mardiyana; Ilham Fajri (International Journal Of Community Service, 2026)
The rapid development of Artificial Intelligence (AI) technology has brought significant changes across various sectors, including education. One of the major challenges faced by educators is how to deliver learning materials in an engaging, creative, and interactive manner so that students can more easily understand the concepts being taught. Islamic boarding schools (pesantren), as faith-based educational institutions, play a strategic role in shaping morally grounded and competitive generations. However, teaching and learning processes in pesantren are generally still dominated by traditional methods that lack variety, which may reduce students’ learning motivation. This community service program aims to improve the quality of learning through the implementation of AI-based instructional media at Pesantren Agrobusiness Tunas Quran. The approach integrates digital technology with storytelling techniques to create learning experiences that are interactive, creative, and contextually relevant. The program activities include training teachers in the use of AI for developing instructional media, mentoring the implementation of AI-supported learning in the classroom, and evaluating the effectiveness of the applied methods. The expected outcomes of the program include enhanced pedagogical and technological competencies of teachers, increased learning motivation among students, and the availability of innovative and sustainable instructional media. Furthermore, this program is expected to serve as a model for digital transformation in pesantren, enabling them to adapt to technological advancements while preserving Islamic values. The results of the training demonstrate that the “Training on the Utilization of Artificial Intelligence in Developing Instructional Media at Pesantren Agrobusiness Tunas Quran, Bandung Regency” was highly effective and well received by the participants.